2022
DOI: 10.1039/d2sm00482h
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of viscoelastic characterization in multi-harmonic atomic force microscopy

Abstract: This study discusses the sensitivity of viscoelastic characterization to multi-frequency atomic force microscopy observables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In a mathematically simpler power-law viscoelastic model, it was recently demonstrated that the structure of the l 2 norm contained many local minima which resulted in frequent misidentifications of θ . 82 In Fig. 5a and b, we show the surfaces of the norm for both the time l t 2 and frequency l ω 2 domain models for a wide range of parameter space around the true minimum ( G̃ 1obs = 0.5, 1obs = 0.5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a mathematically simpler power-law viscoelastic model, it was recently demonstrated that the structure of the l 2 norm contained many local minima which resulted in frequent misidentifications of θ . 82 In Fig. 5a and b, we show the surfaces of the norm for both the time l t 2 and frequency l ω 2 domain models for a wide range of parameter space around the true minimum ( G̃ 1obs = 0.5, 1obs = 0.5).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if the surface of the l 2 norm encompasses regions of h for which the values of the norm are below the machine precision level, the computer will not be able to reliably distinguish between h's in these areas and the algorithm will also be unable to continue advancing towards the minimum. 86 In a mathematically simpler power-law viscoelastic model, it was recently demonstrated that the structure of the l 2 norm contained many local minima which resulted in frequent misidentifications of h. 82 In Fig. 5a and b, we show the surfaces of the norm for both the time l t 2 and frequency l o 2 domain models for a wide range of parameter space around the true minimum (G ˜1obs = 0.5, t1obs = 0.5).…”
Section: Analysis a Insensitivity Of The L 2 Normmentioning
confidence: 96%
See 1 more Smart Citation
“…[17] Due to the dynamic nature of advanced AFM techniques, during the nonlinear interaction between the cantilever-tip ensemble and specimen, higher harmonics of the fundamental frequency of the vibrating cantilever emerge. [18][19][20] The main source of these harmonics' responses is short-range attractive and repulsive forces as well as contact time. As a consequence, these harmonics carry plentiful information on the mechanical, physical, and chemical properties of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, these harmonics carry plentiful information on the mechanical, physical, and chemical properties of the specimen. [18,20] Recent studies demonstrated the harmonics of microcantilever signal are highly sensitive to the local elasticity of the materials, [18,21] and higher contrast with detailed imaging were achieved from the higher harmonics of the microcantilever signal rather than its fundamental frequency. [22,23] Hence, using harmonic amplitude images with higher spatial resolution can open a path for fast, robust, and non-invasive mapping of mechanical, physical, and chemical properties of advanced materials at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%